Representasi Makna Religius dalam Lirik Lagu “33x” Karya Band Perunggu - Latifath Ahfa, De Mimam; Ummu Salamah; Heri Hendrawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Music becomes section of a communication process where the message conveyed in song lyrics carries a special meaning, as seen in the lyrics of the song